SOCIO-PSYCHOLOGICAL FACTORS OF ADAPTATION - Sadiqova Gulbarno Odiljon kizi (Ecominds Press, 2025)
The article discusses the psychological changes of adolescence, the problem of adaptation, adaptation, emotional experiences in them, learning, sensitivity, educational activities, the desire for activity and independence in adolescents, communication with peers.
Keywords: Adolescence, adaptation, adaptation, individuality, creative activity, sensitivity, emotion, fear, communication, perception, imagination.